The relationship between loneliness, nomophobia, and psychological well-being of migrant students - Haula Karimah; Agus Sukirno; Yogi Damai Syaputra (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2025)
Purpose – This study aims to see the extent of the relationship between loneliness, nomophobia, and psychological well-being of Maulana Hasanuddin Islamic University Banten. Method – This study involved 69 students who were selected using convenience sampling techniques, class of 2020-2023. The measuring instruments used in this study were loneliness, nomophobia, and psychological well-being. Result – The results of this study indicate a negative and significant relationship between the three variables, namely loneliness, nomophobia and psychological well-being of migrant students. Based on the findings of the study, it shows that migrant students who feel lonely will be more dependent on smartphones as a source of connection to their social networks. This can lead to increased nomophobia, and reduce their psychological well-being. If migrant students experience anxiety when they cannot use their smartphones, this will worsen feelings of loneliness and reduce psychological well-being. Implication – The importance of the results of this study can be a basis for campuses and counseling service institutions to design interventions that support mental health, such as programs to improve social skills, stress management, and healthy digital literacy to prevent dependence on gadgets as an escape from social isolation. Originality/Value – This study examines the relationship between three psychological variables simultaneously, namely loneliness, nomophobia, and psychological well-being, specifically in the group of migrant students. This study provides a new perspective on the factors that influence the psychological well-being of students in the context of educational mobility and technological progress.